2024
DOI: 10.3390/jfb15020043
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification Strategies for Chrysin-Loaded Iron Oxide Nanoparticles to Boost Their Anti-Tumor Efficacy in Human Colon Carcinoma Cells

Aynura Karimova,
Sabina Hajizada,
Habiba Shirinova
et al.

Abstract: Enhancing nanoparticles’ anti-cancer capabilities as drug carriers requires the careful adjustment of formulation parameters, including loading efficiency, drug/carrier ratio, and synthesis method. Small adjustments to these parameters can significantly influence the drug-loading efficiency of nanoparticles. Our study explored how chitosan and polyethylene glycol (PEG) coatings affect the structural properties, drug-loading efficiency, and anti-cancer efficacy of Fe3O4 nanoparticles (NPs). The loading efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Polyvinyl alcohol (PVA)-coated IONPs induced IL1β levels in monocytes without affecting their survival [57]. Karimova et al demonstrated that chitosan and polyethylene glycol coatings affect the structural properties, drug-loading efficiency, and anti-cancer efficacy of Fe3O4 nanoparticles [58]. In the study of Bhattacharya et al design of dual temperature and pH responsive polymer integrated magnetic nanohybrids comprising of smart block copolymers and mixed ferrite nanoparticles for efficient anti-cancer drug delivery and magnetic resonance imaging [59].…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA)-coated IONPs induced IL1β levels in monocytes without affecting their survival [57]. Karimova et al demonstrated that chitosan and polyethylene glycol coatings affect the structural properties, drug-loading efficiency, and anti-cancer efficacy of Fe3O4 nanoparticles [58]. In the study of Bhattacharya et al design of dual temperature and pH responsive polymer integrated magnetic nanohybrids comprising of smart block copolymers and mixed ferrite nanoparticles for efficient anti-cancer drug delivery and magnetic resonance imaging [59].…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%